MS Office Optimization Assistance for Residents and Village Officials of the Blanceran Village Government, Klaten Regency - Wiharto; Siti Fatimah; Mulyanto (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Blanceran Village, Klaten Regency is one of the villages in Klaten which has quite good potential for natural resources and human resources. This is demonstrated by the existence of a variety of adequate village facilities (computers and village WIFI). The existence of these things has not been able to be utilized properly because of the limited knowledge possessed by residents, giving rise to various very complex problems. Problems in the field of law and the use of technology to support village governance. In the legal field, there are many problems regarding the existence of Village Regulation regulations that have not been properly legalized. This raises the consequences of debate and friction between citizens in overcoming a problem. In the field of informatics there is a problem that so far, the village government has computer facilities, but it has not been maintained properly because human resources are not yet available properly so that it seems the computer is stalled and not being used properly. The solution is to provide education about optimizing the use of computers, especially MS Office. Village apparatus and prospective village apparatus require assistance to improve soft skills and computer optimization to lighten the workload. This can also be applied, especially in filing Village Regulation (PERDES) documents. The results of this service had a significant impact, namely 99% of residents and village officials experienced an increase in knowledge.